PERAN SUFISME DALAM MENGATASI PAHAM ISLAM RADIKAL DI INDONESIA - Abshor, Ulil (Pascasarjana UIN ANTASARI Banjarmasin, 2019)
Radical Islamic Movement or Islamic Radicalism is a movement that has a mindset of textualist ideology, takfiri and truth claim. Basically, the context in which a religious understanding that is claimed to be the final truth, certainly contains an exclusive and offensive element so that some views, flow, and any schools outside is deemed as deviant, because it is far from authoritative sources originating from the Qur'an and the Sunna. This phenomenon does not reflect the peace of Islam as taught by the Prophet as rahmatan lil ?Alamiin (mercy for all nature). This article explores further the importance of the role of Sufism related to the spiritual teachings in it which are the basic foundation in realizing Islam that is peaceful, tolerant, respectful, respectful among fellow human beings especially among other religious people. Islamic teachings extracted in Sufism contain solutive elements in fulfilling the true spirit of Islamic migration (hijra). The Sufism values contain restraints on an